The Use of Symbolism in Zora Neale Hurston’s Their Eyes Were Watching God (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper examines the symbolic elements in Zora Neale Hurston’s novel Their Eyes Were Watching God, focusing on how key symbols—such as the pear tree, the horizon and Janie’s hair—enrich the narrative’s thematic depth. The pear tree symbolizes Janie’s idealized vision of love and harmony, establishing the foundation for her lifelong pursuit of self-realization. The horizon represents her dreams and the boundless possibilities that life holds, reflecting her evolving sense of purpose. Janie’s hair emerges as a striking symbol of her autonomy, strength and defiance of restrictive social conventions. Through these powerful images, Hurston vividly charts Janie’s journey toward self-discovery, empowerment and inner freedom. This analysis underscores how Hurston’s use of symbolism enhances the reader’s understanding of Janie’s experiences and illustrates her ultimate triumph in achieving an authentic and self-defined existence.